Comparison of anthropometric indices of obesity to predict hypertension among young medical students - Lahole, Swapnil; Rawekar, Rajendra; Wanjari, Anil (International Journal of Psychosocial Rehabilitation, 2020)
Obesity is a risk factor for Hypertension1. Early detection of hypertsion is essential in young population and to detect best and trustable predictor for risk population and and also for planning prevention statergy2. In this study we are using anthropometric indices like Body mass index, neck circumference, waist to hip ratio values to predict hypertension among young medical students.are as follows To determine the accuracy of anthropometric indices of obesity to predict hypertension among young medical students.To determine the prevalence of hypertension and pre hypertension among young medical students.Methodology It is a cross sectional study. Setting: This study will be carried out in J. N. Medical College, Sawangi (Meghe), Wardha, which is a rural based medical college in state of Maharashtra. Study will be done among MBBS undergraduate in 1000 students of this college. It is planned to do this study from 1st August 2018 to 31st July 2020.Blood pressure and anthropometric indices and blood samples will be collected in medicine opd in five settings. We will enter the data in Microsoft excel sheet and will analyse that with STATA version 13 statistical software.Results There will be increase in mean values of all anthropometric indices in study population and increase in all anthropometric indices in female as compare to male significantly exception is WHR. Systolic BP and Diastolic BP is correlated with all anthropometric indices of obesity which shows BMI had topmost correlation coefficient and conicity index had low most correlation coefficient. Predictive potential is highest for hypertension, BMI, WC and WHtR In both male and female. Increase in anthropometric index with one standard deviation will lead to increase in hypertension prevalence ration.There will be strong association Systemic hypertension with BMI,WHtR . Anthropometric indices will have in male gender will have better predictive potential for prediction of hypertension.